1977
DOI: 10.1021/j100528a017
|View full text |Cite
|
Sign up to set email alerts
|

Standards for magnetic measurements. A comparison and a proposal for the use of tetramethylethylenediammonium tetrachlorocuprate(II)

Abstract: The magnetic properties of three compounds which are appropriate as magnetic susceptibility standards have been studied in detail. A new value of -1.86 ± 0.01 K has been determined for the Weiss constant of HgCo(NCS)4, and the zero-field splitting parameter, D, has been found to be +19 ± 3 cm1 with g being 2.22 ± 0.03. The magnetic data for bis(2,2'-bipyridine)thioureacopper(II) perchlorate may be reproduced accurately from the expression M = Ng¡/¡JB3(X) where B3(X) = [(2-7 + l)/2J] coth ([(2J + 1)/2J]X| -(1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 1 publication
1
30
0
Order By: Relevance
“…Such levels above the ground state may not contribute to the magnetic susceptibility [20]. Similar behaviour has been observed for Sm 2 WO 6 and cm 3 /g reported by Brown et al [22] or T -. and F 0 = 0.48410 -6 cm 3 /g reported by Nelson and ter Haar [23].…”
Section: Magnetic Propertiessupporting
confidence: 84%
“…Such levels above the ground state may not contribute to the magnetic susceptibility [20]. Similar behaviour has been observed for Sm 2 WO 6 and cm 3 /g reported by Brown et al [22] or T -. and F 0 = 0.48410 -6 cm 3 /g reported by Nelson and ter Haar [23].…”
Section: Magnetic Propertiessupporting
confidence: 84%
“…The best-fit parameters obtained are: g Co = 2.336(1), J = Ϫ144(2) cm Ϫ1 and |D| = 31.9(1) cm Ϫ1 for complex 2: g Co = 2.442(4), J = Ϫ195(26) cm Ϫ1 and |D| = 21.4(5) cm Ϫ1 for complex 2Br. Since the obtained g Co and |D| values are considered to be acceptable in view of the corresponding parameters of the other tetrahedral Co II complexes concerned, 21 it can be concluded that the magnetic coupling between Co II and IMmepy is largely antiferromagnetic.…”
Section: Cobalt(ii) Complexes With Immepymentioning
confidence: 88%
“…This balance has an accuracy of 2 J.lg. The calibration of H F was carried out by a measurement on z HgCo(SCN)4, which has a mass susceptibility of 16.44 x 10 -6 cm'/g at 20°C [10]. The sample container was held in a double cylinder of glass in which temperatures were attained with a thermostated liquid.…”
Section: Methodsmentioning
confidence: 99%